2020
DOI: 10.3390/ijms21228486
|View full text |Cite
|
Sign up to set email alerts
|

A SINE-VNTR-Alu in the LRIG2 Promoter Is Associated with Gene Expression at the Locus

Abstract: The hominid SINE-VNTR-Alu (SVA) retrotransposons represent a repertoire of genomic variation which could have significant effects on genome function. A human-specific SVA in the promoter region of the gene leucine-rich repeats and immunoglobulin-like domains 2 (LRIG2), which we termed SVA_LRIG2, is a common retrotransposon insertion polymorphism (RIP), defined as an element which is polymorphic for its presence or absence in the genome. We hypothesised that this RIP might be associated with differential levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…SVA retrotransposons are known to be active in the human genome, are frequently associated with disease, ( 35,36 ) and have been shown to alter local methylation patterns. ( 37 ) A similar insertion at this position was not found in public genome databases or after analysis of nearly 14,000 whole short‐read genomes of unrelated individuals.…”
Section: Discussionmentioning
confidence: 80%
“…SVA retrotransposons are known to be active in the human genome, are frequently associated with disease, ( 35,36 ) and have been shown to alter local methylation patterns. ( 37 ) A similar insertion at this position was not found in public genome databases or after analysis of nearly 14,000 whole short‐read genomes of unrelated individuals.…”
Section: Discussionmentioning
confidence: 80%
“…However, intron retention is not operating at the MAPT locus as the SVA is intergenic in nature ( Figure 1 ). To date, studies have focused predominantly on differential gene expression analyses, however, these approaches are limited as they do not account for isoform diversity ( Makino et al, 2007 ; Hancks and Kazazian, 2010 ; Gianfrancesco et al, 2017 ; Hall et al, 2020 ). Many of the genes at this locus have been associated with CNS functional parameters ( Caillet-Boudin et al, 2015 ; McEwan et al, 2015 ; Moreno-Igoa et al, 2015 ; de la Tremblaye et al, 2017 ) and encode more than one isoform which are generated, for instance, through mechanisms such as alternative splicing or alternative usage of transcription start sites ( Elkon et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the small nuclear RNA U4atac Pseudogene 9 (RNU4ATAC9P) may be involved in minor spliceosome function. Traditionally thought to be non-functional, recent studies have suggested that pseudogenes, and types of pseudogenes like retrotransposons, may play a regulatory role in gene expression (34,35). The similarity of the CABS1 UGR to these other UGRs could provide clues to how CABS1 is regulated in the body and perhaps some of its functions.…”
Section: Discussionmentioning
confidence: 99%